Fishing Ship Trajectory Tracking Control Based on the Closed-Loop Gain Shaping Algorithm Under Rough Sea - Song, Chun-yu; Guo, Te-er; Sui, Jiang-hua (China ocean engineering, 2025)
This paper proposes a separated trajectory tracking controller for fishing ships at sea state level 6 to solve the trajectory tracking problem of a fishing ship in a 6-level sea state, and to adapt to different working environments and safety requirements. The nonlinear feedback method is used to improve the closed-loop gain shaping algorithm. By introducing the sine function, the problem of excessive control energy of the system can be effectively solved. Moreover, an integral separation design is used to solve the influence of the integral term in conventional PID controllers on the transient performance of the system. In this paper, a common 32.98 m large fiberglass reinforced plastic (FRP) trawler is adopted for simulation research at the winds scale of Beaufort No. 7. The results show that the track error is smaller than 3.5 m. The method is safe, feasible, concise and effective and has popularization value in the direction of fishing ship trajectory tracking control. This method can be used to improve the level of informatization and intelligence of fishing ships.